Ab initio calculation of the electronic structure of Fe and Cr interlayers - Ahmad Zabidi, N.; Abu Kassim, H.; Shrivastava, K.N. (2010)
The band structure, 'diversity of structure and various band gaps have been calculated using ab initio density functional theory (DFT) for some interlayer structures consisting of Fe and Cr atoms, viz. (a) Fe-Cr, (b) Fe-Fe-Cr-Cr and (c) Fe-Fe- Cr-Cr-Fe-Fe-Cr-Cr. Calculations have been done for spinpolarized as well as unpolarized orbitals. The spins are shown to affect the band gaps and resistivity considerably. As a test, We also obtained the band structure of Fe and Cr bulk unit cells. An effort is made to discuss the resistivity as a function of spin.